Attention-Deficit/Hyperactivity Disorder: A Current Overview - Banaschewski, Tobias (Dtsch Arztebl Int, 2017)
BACKGROUND: Attention-deficit/hyperactivity disorder (ADHD) is a common, early-onset, persistent developmental disorder of childhood and adolescence, with a prevalence of approximately 5%. METHODS: This article is based on publications retrieved by a selective search in PubMed with an emphasis on pertinent guidelines and systematic reviews. RESULTS: At least 75% of affected children and adolescents develop a comorbid disorder, which impedes diagnosis and treatment and worsens prognosis. The etiology of ADHD is complex and heterogeneous, involving a major genetic component and diverse neurobiological alterations. Prenatal environmental factors also seem to elevate the risk of ADHD. The mainstays of treatment are psychoeducation, behavioral therapy, and psychoactive drugs, which generally have only mild side effects, such as insomnia or decreased appetite. The indication for treatment in the individual case is based on severity, comorbidity, previous therapy attempts, and the familial, social, and educational framework conditions. CONCLUSION: Translational research is needed to clarify the etiology of ADHD. Epidemiological studies published since 1987 do not reveal any increase in the prevalence of ADHD among children and adolescents. Improved diagnosis necessitates an evidence-based and need-adapted approach to treatment.